DEMOCRACY AND SOCIAL INEQUALITY - S. M. Eliseev (Дискурс)
The article analyzes the long-term impact of democratic institutions on socio-economic and political development of modern society. The author proves that the transitions to democracy in the twentieth century accelerated not only the pace of economic development, but also the processes of social polarization in society. Despite the positive impact of democratic institutions on economic development and political stability, democracy as a form of political rule cannot solve the problem of social inequality. The history of modern democracy shows that it reduces inequality levels only in certain cases, and in most cases social inequality increases both at the national and global levels.